(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The importance of beauty and personality is increasing now a day as it is a competitive era. The urge of need of using perfumery and cosmetic was nurtured when person started using them. Need of beautification was correlated with attraction. The Indian tradition of perfumery and cosmetic is very old. Sweating is a normal physiological process; sweat is 99% water with some salt (NaCl), vitamin C, anti-bodies, traces of metabolic wastes and lactic acid composition. It’s a natural process to cool the body temperature. Thermal and emotional factors promote sweating. The moist environment created by Hyperhidrosis condition, creates an ideal conditions for an overgrowth of bacteria. Hyperhidrosis condition, bacteria break down certain proteins in the sweat into acids, so it is not the bacteria that stink. It is the by-product of the bacteria breaking down the protein. As we are living in the industrial era, where the problem of global warming a matter of great concern and is increasing radically, as a result of increasing temperature. People are suffering from excessive sweating and some people also posses bad odor with sweating. This situation will bring a huge psychological and social burden, because it will interferes with daily activities. Many people do not seek medical help because they do not know that their condition requires medical intervention. Due to excessive sweating it can cause various infections. Many people use antiperspirants products to control sweating and body odor. Some chemical antiperspirants are effective; however, the side effects like irritations, discoloration allergy, are also obvious.